Symptomatic Maxillary Sinus Retention Cyst Following a Prior Sinus Perforation: A Case Report - Arta Sinanaj Demiri; Shaqir Demiri; Edin Demiri; Besir Salihu (Case Reports in Dentistry)
Maxillary sinus retention cysts (MSRCs) are benign, fluid-filled lesions most often discovered incidentally on radiographic imaging. Although typically asymptomatic, larger cysts may lead to clinical symptoms due to pressure on surrounding sinus structures. This report presents a rare symptomatic case of an MSRC in a 70-year-old female patient with a prior history of sinus perforation following upper molar extraction. The patient experienced severe unilateral facial pain, nasal congestion, debilitating headaches, and dizziness over a 6-month period. Radiographic imaging (CT scan) revealed a well-circumscribed, dome-shaped lesion in the right maxillary sinus without signs of bone erosion. Given the failure of conservative management and the intensity of symptoms, surgical intervention via the Caldwell–Luc approach was performed. Intraoperatively, the cystic lesion was enucleated and sent for histopathological examination. Histology confirmed a benign retention cyst lined with respiratory epithelium, along with inflammatory infiltrates and the unusual presence of cholesterol crystals, which is an uncommon finding in MSRCs. The patient’s history of sinus perforation likely contributed to chronic inflammation and cyst formation. This case emphasizes the importance of considering dental history, particularly previous maxillary molar extractions with sinus involvement, in patients presenting with atypical sinus symptoms. While endoscopic sinus surgery is often the preferred approach, the Caldwell–Luc procedure remains valuable in selected cases with complex anatomy or previous surgical alterations. Clinicians should be aware of rare presentations of MSRCs that may require tailored surgical management for symptom resolution and recurrence prevention.